2018
DOI: 10.1111/lre.12248
|View full text |Cite
|
Sign up to set email alerts
|

Identification of critical control points using water quality as an indicator of hygiene for artisanal fisheries on Lake Malawi

Abstract: Fish are a highly perishable commodity, and unhygienic fresh fish supply chains have been documented over the past two decades in sub‐Saharan Africa. Fishers spend long hours on boats with no provision of sanitary facilities, and even after landing, they are often in environments without sanitary facilities. The purpose of the present study was to explore the impacts of water, sanitation and hygiene practices in an artisanal fishery on food safety by analysing water samples in close contact with fresh fish at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…For instance, a recent study in South Africa found that the provision of safe water contributed to an eight-fold decrease in children’s risk of urogenital schistosomiasis infection [ 10 ]. Risk factors contributing to periodic diarrhoea and cholera outbreaks in fishing populations have included: Lack of access to sanitary facilities and potable water for fishermen while fishing, overcrowding on the beaches, poor water quality, low levels of hygiene, and poor waste management [ 2 , 11 , 12 ]. These problems are compounded by the lack of sanitation and hygiene facilities in these populations [ 2 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, a recent study in South Africa found that the provision of safe water contributed to an eight-fold decrease in children’s risk of urogenital schistosomiasis infection [ 10 ]. Risk factors contributing to periodic diarrhoea and cholera outbreaks in fishing populations have included: Lack of access to sanitary facilities and potable water for fishermen while fishing, overcrowding on the beaches, poor water quality, low levels of hygiene, and poor waste management [ 2 , 11 , 12 ]. These problems are compounded by the lack of sanitation and hygiene facilities in these populations [ 2 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding population health impacts, safe water, hygiene practices, and hygienic production processes are similarly vital to ensure that fresh fish and fish products, a key source of income and food security, are wholesome [ 14 , 15 ]. Care in fish handling is paramount, particularly between capture, processing, and vending of fish, because the quality, safety, and shelf life of the products are dependent on proper handling and processing practices [ 12 , 14 , 15 ]. Studies in Malawi have shown that there is a high risk for microbial contamination at all stages from capture to sale of fresh fish from artisanal fishermen, and this was significant across all seasons [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Heinitz, Ruble, Wagner, & Tatini, ; Hansen, Clark, Ishii, Sadowsky, & Hicks, ; Food and Agriculture Organization of the United Nations [FAO], ). However, contamination can occur along the supply chain, as fish are handled by several intermediaries from the time of capture to sale at local markets (Samikwa, Kapute, Tembo, Phiri, & Holm, ). Heinitz et al () found a 12.2% incidence of Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%